Mısır şuruplarında enzimatik olmayan esmerleşme reaksiyonları ve şuruplarda raf ömrü tespiti - Bostan, Alin (Fen Bilimleri Enstitüsü, 1997)
Cargill Vaniköy Tarım San. ve Tic. A.Ş.'den temin edilen mısır şuruplarında 25°C, 35°C, 45°C ve 55°C'lerde 11 haftalık depolama sürecinde optik yoğunluklarındaki artışın izlenmesi yoluyla enzimatik olmayan renk esmerleşmesi (Maillard reaksiyonu)nin kinetiği belirlenmiş ve çalışılan şurupların bu şartlar altındaki raf ömürleri saptanmıştır. İncelenen şuruplar 38 ve 59 DE olmak üzere iki farklı dekstroz eşdeğerine sahip olup, her birinin pH değeri 4.0, 4.5 ve 5.0'e ayarlanmıştır. Çalışmada her şurubun bir adet paralel numunesi kullanılmıştır. 25°C ve 35°C'lerde depolanan şurupların renklerinin 11 haftalık depolama süresi sonunda sararmaması ve hesaplanan optik yoğunluk değerlerinde de artış olmamasından dolayı bunlar değerlendirmeye alınmamıştır. Şuruplarda hesaplanan en uzun raf ömrü pH 4.0 ve 45°C'de 21.5 hafta, en kısa raf ömrü ise pH 5.0 ve 55°C'de 8.5 haftadır. Bu şurupların renk koyulaşma reaksiyonu hız sabitleri ise sırasıyla k=0.146 (r=0.7728) ve k=0.400 (r=0.9904) hafta'dir. Çalışma sonucunda, mısır şuruplarının depolama sıcaklıkları olarak, deneysel çalışma boyunca renkte tespit edilebilir bir değişikliğin görülmediği 25°C ve 35° C'lerin seçilmesi önerilmektedir. Ancak bu önerinin getireceği ilave maliyet fizibilite çalışmaları ile de değerlendirilmelidir. Diğer bir öneri ise depolama ve taşıma pH değerleri olarak pH 4.0'ün seçilmesidir. Çalışma sonucunda saptanan bir diğer önemli husus ise çalışmada incelenen koşullardan herhangi birine maruz kalmış olan şurupların sakkarit bileşimlerinde pH veya sıcaklığa bağlı olarak anlamlı bir değişiklik olmamış olmasıdır. Bu çalışma sonunda, şurupların depolama ve taşınması için önerilen sıcaklık ve pH değerleri ile renkteki sararmanın aslında şurubun fonksiyonel özelliklerini, bir diğer deyişle kullanım yerini değiştirmeyeceğinin saptanmış olması şurubun kullanıcısı olan sanayiciler açısından pratik fayda sağlayacak sonuçlardır.

Glucose syrups are starch hydrolysis products that contain the sugar glucose as well as higher molecular weight dextrins and saccharides. They are clean, colorless and nutritional sweeteners with texture. The European Community (EC) and the Codex Alimentarius Commission (CAC) define the glucose syrup as: " a purified concentrated aqueous solution of nutritive saccharides obtained from edible starch by controlled partial hydrolysis" (HOWLING, 1984a; HOWLING, 1984b). Corn, potato and wheat starch are used as raw material for syrup manufacture and the product is named as "corn syrup" in USA since corn is the major source for its production (HOWLING, 1984a; HOWLING, 1 984b; HEBEDA, 1987). Corn syrups were first discovered in 1811 by the German chemist Kirchoff who obtained a sweet syrup by boiling starch with dilute acid. The discovery was evaluated economically and industrial production started using wheat starch as raw material in Germany. Later on, potato starch was used to obtain a cleaner and a sweeter syrup. The industry made progress in the early 19th century in Europe and USA started to use corn as raw material (HOWLING, 1984a). The production of corn syrups started in batch systems with the use of mineral acids; later continuous systems gradually became available. In 1938, the first trial for production with enzymes was made with a fungal amylase, leading to sweeter and less textural syrups and thus to a 68-86% increase in production during 1940-42 (HEBEDA, 1987). The success gave the idea of using enzymes in the production line and in the 1960's, acid- enzyme processes were developed in order to produce higher glucose containing syrups. In the 1970's, with the presentation of thermally resistant bacterial alfa- amylase to industry, processes using only enzymes were developed and a net increase in glucose production was obtained. Technological progress made in the other units of the production line, such as the purification or the refining units with carbon and several ion exchange resins, made it possible to obtain thermally resistant glucose syrups with desirable color (HOWLING, 1984b). Corn syrups are used in many food formulations. Generally, in the world market, the confectionery industry holds the lead in their use (HOWLING, 1984b). The other important fields of use are jams and marmelades, alcoholic and non alcoholic beverages, bakery products, seasonings and the fruit processing industry. Besides their sweetening function, corn syrups give the product resistance for moisture changes in the environment (humectancy), moisture absorbance properties (hygroscopicity), cohesiveness ; they also control or prevent crystallization, decrease IX freezing point of product to prevent the formation of ice crystals, increase osmotic pressure to prevent microbial action, give brightness to product, balance flavor of product during the chewing process by enhancing desired flavors and masking the others, provide the carbohydrates necessary for yeast action in fermented products such as bread and beer and enhance melting properties of product (HOWLING, 1984a; HOWLING, 1984b; JUNK and PANCOAST, 1973; HANOVER, 1982; LIAH-LOH, 1984; JACKSON, 1990a). The initial "water- white" nature of corn syrups is temporary, since when either stored or processed, the development of first yellow, then a brown color is observed due to non-enzymatic Maillard browning reactions (JACKSON, 1990b). The brown color formation in corn syrups is due to the Maillard reactions that occur between the sugar components of the syrup and residual proteins from corn. Although the formation of end-products from Maillard reactions and the resultant color are desirable in the thermal processing of many products such as meat, coffee and bread, their formation during storage of initially white products is undesirable and leads to a reduction in quality (BALIES, 1982). In the case of corn syrup production, the formation of colors and odors greatly affects the sensorial properties such as appearance and flavor, also providing an index of purity. It has been shown previously that Maillard reactions occuring in corn syrups may contribute to syrup discoloration (RAMCHANDER and FEATHER, 1975). Discoloration of the corn syrup during the manufacture of high boiled candies can be a serious problem for the confectionery industry as it may lead to the loss of acceptable color and to the development of off-flavors (LEES, 1976; KEARSLEY and BIRCH, 1985). Brown color development in corn syrups is related to the syrup composition, production conditions, effectiveness of the refining steps and finally the storage temperature and duration of storage. The dextrose equivalent being related to the composition of the syrup, is a factor affecting color development whereas the final pH value and the sulfur dioxide content are related with production conditions. Removal of proteins and minerals is another critical step in the production line (SAPERS, 1993). The objective of this study was to follow the the kinetics of non-enzymatic color development in corn syrups during their storage and to predict the shelf life of the product under the chosen conditions of this study. The study was conducted on corn syrups (produced by Cargill Vaniköy Co. Corn Products Division, İstanbul-TURKEY) with two differing dextrose equivalents (DE 38 and DE 59). Samples from each syrup were adjusted to three different pH values (pH 4.0, 4.5 and 5.0) respectively and sub-samples from each were stored at 25°C, 35°C, 45°C and 55°C for 1 1 weeks. The color development in all fortyeight of these syrups was investigated by measuring optical density of each at 420 nm at weekly intervals. The syrups under study were acid- and acid-enzyme hydrolyzed syrups with 37.5 and 58.9 DE values with the tradenames of Vaniköy Standard and Vanitat 58, respectively (Table 1). Table 1. Physical and chemical properties of investigated corn syrups *DP= Degree of polimerization, DP ^monosaccharides, DP 2=disaccharides, DP3=trisaccharides, >DP4=tetrasaccharides and higher oligosaccharides The syrups, when evaluated for their dextrose equivalents, were determined to be of the Types of II and III as they are grouped according to their DE values as follows. a)TypeI 20 - 37 DE b)Type II 38 - 57 DE c)Type III 58 -72 DE d)Type IV 73 DE and over (JUNK and PANCOAST, 1973). The initial pH values of the syrups were 3.35 and 3.46, respectively as they were supplied before pH adjustment in the factory whereas the sulfur dioxide used as an additive was determined to be at 40 ppm level in both syrups. The protein and ash contents of 38 DE and 59 DE syrups were 0.055% and 0.20%; 0.044% and 0.37%, respectively (Table 1). These results are within the specified limits set forth by Cargill Vaniköy Co. Corn Products Division. When evaluated for their carbohydrate profiles (Table 1 ) with HPLC, it was observed that the syrups had typical product compositions (Table 2). XI Table 2. Typical saccharide compositions of Vaniköy Standard, Vanitat 58, acid- and acid-enzyme hydrolyzed syrups a: acid- and acid-enzyme hydrolyzed syrups (CARGILL. 1997a. b) b: acid-hydrolyzed symps (DZIEDZIC and KEARSLEY, 1984;HOBBS, 1986; JACKSON, 1973). c: acid-enzyme hydrolyzed syrups (DZIEDZIC and KEARSLEY. 1984). First order kinetics was used to evaluate experimental data, since the regression analysis of the logarithm of ICUMS A color values and time gave a linear relationship. According to LAB UZA and RIBOH (1982), most quality-related reaction rates are either zero or first-order reactions and statistical differences between the two types may be insignificant. LABUZA (1979) also stated that the error in the value of the reaction rate constant (k) due to the order of the reaction chosen is less than 5% since the calculated statistical difference between zero- and first- order is small. The equation representing this relation is, «"*' . (1) where A is the ICUMSA unit at time t; Ao is the initial value and k is the reaction rate constant. From the slope of each line that represents the increased color development (browning), the reaction rate constants (k) were obtained using lineer regression for each syrup. The kinetic parameters and shelf lives of samples stored at 25°C and 35°C were not calculated because of the insignificance of color changes that occurred at these temperatures (Figures 1-6). xn 3 2.5 i 2 < | 1.5 ö 1 0.5 0 5 10 Time (Week) 15 Figure 1. Color development in corn syrups with time (38 DE, 59 DE; pH = 4.0; T = 25°C, 35 °C) ? 38DE25C D 38 DE 35 C A59DE25C X59DE35C 5 10 Time (Week) 15 Figure 2. Color development in com syrups with time (38 DE, 59 DE; pH = 4.5; T = 25°C, 35°C) Figure 3. Color development in corn syrups with time (38 DE, 59 DE; pH = 5.0; T = 25°C, 35°C) Xlll ? 38DE45C M38DE55C A59DE45C X59DE55C 5 10 Time (Week) Figure 4. Color development in corn synips with time (38 DE, 59 DE; pH = 4.0; T = 45°C, 55°C) ? 38DE45C M 38 DE55C A59DE45C X59DE55C 5 10 Time (Week) 15 Figure 5. Color development in corn syrups with time (38 DE, 59 DE; pH - 4.5; T = 45°C, 55°C) Figure 6. Color development in corn syrups with time (38 DE, 59 DE; pH = 5.0; T = 45°C, 55°C) XIV The shelf lives of samples were calculated according to the relationship: e =i"4-i"4 (2) where 8S is the shelf life of sample in weeks and A* is 200 ICUMSA units (ROBERTSON, 1993). To point out the influence of temperature on reaction rates, the Qio values were calculated according to the relationship: (k ) Qn = -77^ (3) ik.rc) where k^ i0°c and kTüc are the browning reaction rate constants of the syrups at T+10°C and T°C temperatures, respectively. To calculate the activation energy (Ea) of the reaction occuring in each syrup, the following equation was used: k = ktl-e';°RT (4) where ; k0 is the frequency factor, R is the gas constant (1.987 cal/mol K) and T is the absolute temperature in Kelvin. The Qio value indicates how much faster a reaction occurs when a change of 10°C is applied to the reaction. The 1.4-2.4 range determined in this study (45°C- 55°C) was similar to literature data. The Ea values derived on the other hand, were in the range of 8.2-17.5 kcal/mol. The longest acceptable shelf life was 21.5 weeks for syrups at pH 4.0 and 45°C, and the shortest 8.5 weeks at pH 5.0 and 55°C with reaction rate constants of k=0.146 (r=0.7728) and k= 0.400 (r=0.9904) week"1, respectively. The saccharide compositions of the syrups under study were determined by high pressure liquid chromatography both at the start and at the end of storage time and it was observed that there was a slight decrease in the higher saccharides and an increase in the lower saccharide (glucose, maltose and maltotriose) contents of both syrups. This change could be attributed to the gradual hydrolysis of higher saccharides to their mono, di and tri-saccharide units. However, no meaningful difference was observed between syrups with different pH values and stored at different temperatures in terms of their saccharide compositions. xv For both syrups studied, it was observed that shelf-life was the shortest for syrups at pH 5.0 and stored at 55°C. This means that the routine conditions the syrups face are those at which the browning reaction occurs the fastest. Taking this result into consideration, the syrups should be pumped to storage tanks and transportation tankers at 55°C to take advantage of low viscosity at this temperature and then be cooled to 25°C or 35°C, those temperatures at which no considerable color change was measured and should be stored and transported at pH 4.0. However; the additional costs the temperature proposal would present should also be economically evaluated. Another practical result of this study was that there was no considerable change in the saccharide compositions of the syrups that could lead to changes in functional properties, which is an important point for the syrup user. In other words, color development in the syrup will not cause a problem for the user unless he is using it in the manufacture of water-white candies.
Nonenzymatic browning reactions and shelf life predictionof corn syrups
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Esmerleşme reaksiyonları; Mısır; Raf ömrü; Şuruplar; Browning reactions; Maize; Shelf life; Syrups